2009
DOI: 10.1258/jtt.2009.003006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a mobile phone telemonitoring system for glycaemic control in patients with diabetes

Abstract: We conducted a randomized controlled trial using mobile health technology in an ethnically diverse sample of 137 patients with complicated diabetes. Patients in the intervention group (n = 72) were trained to measure their blood glucose with a sensor which transmitted the readings to a mobile phone via a Bluetooth wireless link. Clinicians were then able to examine and respond to the readings which were viewed with a web-based application. Patients in the control arm of the study (n = 65) did not transmit thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(125 citation statements)
references
References 10 publications
4
118
0
3
Order By: Relevance
“…Fortunately, most studies have found that the study participants adapted well to the devices investigated. 22,23,30 Recent developments in smartphones and networks for communication are expected to contribute to the increased use of CPBMI, which in turn is expected to increase the release of mobile medical applications. To promote the stability and reliability of mobile medical applications, assessment criteria should be defined, and official guidelines should be provided for smartphone applications.…”
Section: Technological Improvementsmentioning
confidence: 99%
“…Fortunately, most studies have found that the study participants adapted well to the devices investigated. 22,23,30 Recent developments in smartphones and networks for communication are expected to contribute to the increased use of CPBMI, which in turn is expected to increase the release of mobile medical applications. To promote the stability and reliability of mobile medical applications, assessment criteria should be defined, and official guidelines should be provided for smartphone applications.…”
Section: Technological Improvementsmentioning
confidence: 99%
“…For example, a web-based intervention was designed to support outpatients and healthcare experts to make collaboratively shared decisions in psychopharmacological consultation (Deegan, Rapp, Holter, & Riefer, 2008). Having significant advantages of usability and mobility over these classic systems (Carroll, Marrero, & Downs, 2007;Istepanian et al, 2009), mobile health interventions have been evolved beyond typical data collection and reporting functions ( Van Woensel et al, 2015) to link health observations with health knowledge for better decision quality and outcome (Martínez-Pérez et al, 2014).…”
Section: Shared Decision Makingmentioning
confidence: 99%
“…información para el cuidado de la DT2 16 las intervenciones basadas en el envío de mensajes de texto para el autocontrol de los pacientes con DT2 describieron una mejora en los niveles de HbA1c y destacaron como beneficio adicional el establecer o mejorar la comunicación entre el personal de salud y el paciente 17,18 . La relativa facilidad con la que puede ser enviado un mensaje de texto o short message service (SMS) por sus siglas en Inglés, convierten la utilización del teléfono móvil en un medio de comunicación ideal para el intercambio de información entre el paciente con DT2 y el personal de salud 18,19 .…”
Section: Nº 37 Enero 2015unclassified
“…Los hallazgos de Goodarzi y colaboradores 22 demostraron la efectividad de la intervención utilizando SMS a través del teléfono móvil en el manejo de la DT2 destacando el uso de la telefonía celular para la educación a distancia de estos pacientes. Istepanian y colaboradores 16 no encontraron diferencias en los niveles de HbA1c entre los grupos de intervención y control, describiendo que el envío de SMS no tiene una ventaja sobre el cuidado habitual, sin embargo la intervención tuvo una diferencia en la HbA1c a su favor de 0.64% (P=0.06). El estudio de Shetty y colaboradores 14 demostró que la comunicación a través de los SMS es bien aceptada por los pacientes con DT2 y contribuyo a mejorar los resultados de salud.…”
Section: Tabla 1 Artículos Seleccionados Para Analizarse En La Revisiónunclassified
See 1 more Smart Citation